Large-scale Anisotropy of Galactic Cosmic Rays as a Probe of Local Cosmic-Ray Propagation - Ai-feng Li; Qiang Yuan; Wei Liu; Yi-qing Guo (The Astrophysical Journal, 2024)
Recent studies have shown that the anisotropy is of great value to decipher cosmic rays’ origin and propagation. We have built a unified scenario to describe the observations of the energy spectra and the large-scale anisotropy and called attention to their synchronous evolution with energy. In this work, the impact of the local regular magnetic field (LRMF) and corresponding anisotropic diffusion on large-scale anisotropy have been investigated. When the perpendicular diffusion coefficient is much smaller than the parallel one, the dipole anisotropy points to the LRMF and the observational phase below 100 TeV could be reproduced. Moreover, we find that the dipole phase above 100 TeV strongly depends on the evolution of local diffusion. But the current measurements at that energy are still scarce. We suggest that more precise measurements at that energy could be carried out to unveil the local diffusion and further the local turbulence.